An infrastructure approach for the evaluation of E-Learning - Ebner, Katharina; et al. (International Journal of Knowledge Society Research, 2010)

An Infrastructure Approach for the Evaluation of E-Learning - Ertl, Bernhard; Ebner, Katharina; Kikis-Papadakis, Kathy (Knowledge Management, Information Systems, E-Learning, and Sustainability Research, 2010)

Berufliche Exploration - Ebner, Katharina; Spurk, Daniel (Lexikon der Berufsbildung, 2016)

Career Coaching - Ebner, Katharina; Kauffeld, Simone; Güntner, Amelie (International Handbook of Evidence-Based Coaching, 2022)
This chapter addresses the question of how coaching sessions can take into account clients’ concerns about their career development and discusses the prevalence of this style of coaching in the modern day. We start by describing the concept of career coaching and laying out its potential applications. Next, we go into greater detail by examining how career coaching uses psychometric instruments to evaluate how clients can achieve the optimal person-job fit in their professional development. We present VaMoS as an example to illustrate how clients’ career-relevant values, motives, and competencies can be assessed in order to match them to the perfect job. Finally, we discuss open questions and make suggestions for future researc
Keywords: Career coaching; Coaching methods; Career management; Person-job fit; Career

Career Decision Making: Relationships with Constructs Related to Employability and Initial Validation of the German Career Decision Making Profile - Ebner, Katharina; Thiele, Lisa; Kauffeld, Simone; Spurk, Daniel (17th Congress of the European Association of Work and Organizational Psychology, 2015)

Coaching as Stress-Management Intervention. A Framework of Coaching, Self-Leadership and Coping - Ebner, Katharina; Schulte, Eva-Maria; Kauffeld, Simone (76th Annual Meeting of the Academy of Management, 2016)

Coaching as stress-management intervention: The mediating role of self-efficacy in a framework of self-management and coping - Ebner, Katharina; Schulte, Eva-Maria; Soucek, Roman; Kauffeld, Simone (International Journal of Stress Management, 2017)

Das Modell des studentischen Peer-Coaching an der Universität der Bundeswehr - Lang-von Wins, Thomas; Ebner, Katharina (Universitäre Bildung - Fachidiot oder Persönlichkeit, 2012)

Der Einfluss von Karriereentscheidungsstrategien auf Karriereerfolg, Motivation und psychologisches Wohlbefinden - Ebner, Katharina; Paul, Karsten (11. Tagung der Fachgruppe Arbeits-, Organisations- und Wirtschaftspsychologie der Deutschen Gesellschaft für Psychologie, 2019)

Die Erfassung von Kompetenzen und Potenzialen - Ebner, Katharina (Zukunftsfeld Bildungs- und Berufsberatung, 2010)

Die Reduktion von Karriereeinstiegssorgen durch systemisches Kurzzeit-Karrierecoaching für Studierende - Ebner, Katharina (52. Kongress der Deutschen Gesellschaft für Psychologie (DGPs) (Conference canceled), 2020)

Digitaler Stress: Der inkrementelle Beitrag technologiebezogener Einstellungen und Verhaltensweisen auf technologieinduzierten Stress - Ebner, Katharina; Sende, Cynthia (0th Fachgruppentagung Arbeits-, Organisations- und Wirtschaftspsychologie der Deutschen Gesellschaft für Psychologie, 2017)

Ebner, K., Greif, S., & Kauffeld. E. (2018). Humanressourcen und Personalentwicklung [Human Resources and Personnel Development]. In S. Greif & K.-C. Hamborg (Eds.), Methoden der Arbeits-, Organisations- und Wirtschaftspsychologie. Enzyklopädie der Psychologie (S. 145-213). Göttingen: Hogrefe. - Ebner, Katharina (Methoden der Arbeits-, Organisations- und Wirtschaftspsychologie, 2018)
Keywords: Humanressourcen; Personalentwicklung; Personal; Personnel Development; Personalpsychologie

Employable because of what you do or how you are? The contribution of career decision-strategies on employability beyond personality. - Ebner, Katharina; Soucek, Roman; Thiele, Lisa (5th International Conference for Well-Being and Performance, 2016)

Entscheidungsstrategien während der beruflichen Erstexploration und ihr Einfluss auf eine zukunftsorientierte Laufbahnplanung - Ebner, Katharina; Soucek, Roman; Kauffeld, Simone (9. Fachgruppentagung Arbeits-, Organisations- und Wirtschaftspsychologie der Deutschen Gesellschaft für Psychologie, 2015)

Entwicklung der Studierfähigkeit als Aufgabe der Universität: Coaching studentischer Selbstmanagementkompetenzen - Ebner, Katharina (Zeitschrift für Hochschulentwicklung, 2010)

Evaluation eines Blended Trainings zur Förderung psychologischer Faktoren der Medienkompetenz - Sende, Cynthia; Soucek, Roman; Ebner, Katharina (11. Tagung der Fachgruppe Arbeits-, Organisations- und Wirtschaftspsychologie der Deutschen Gesellschaft für Psychologie, 2019)

Incongruities between values, motives, and skills: Exploring negative effects of self-exploration in career coaching - Ebner, Katharina; Soucek, Roman; Kauffeld, Simone (British Journal of Guidance & Counselling, 2020)

Karriere als Thema im Coaching: Klienten unterstützen, Karriereentscheidungen zu treffen - Kauffeld, Simone; Güntner, Amelie; Ebner, Katharina (Handbuch Schlüsselkonzepte im Coaching, 2016)

Karrierecoaching - Ebner, Katharina; Volmer, Judith (Lexikon der Berufsbildung, 2016)

Karriereoptimismus im Karrierecoaching fördern und messen - Ebner, Katharina (Organisationsberatung, Supervision, Coaching, 2020)
Karrierecoaching ist ein Coachingformat, das sich steigender Nachfrage erfreut. Trotz ihrer praktischen Bedeutsamkeit ist diese Dienstleistung aber inhaltlich unscharf definiert und ihre Wirkung empirisch schwach belegt. Der Beitrag begegnet diesem Mangel, indem Karriereoptimismus als Arbeitsziel im Karrierecoaching eingeführt wird. Karriereoptimismus wird als Sonderform situativen Optimismus vorgestellt und in der empirischen Befundlage zum Karrierecoaching verortet. Die positive Wirkung von Karriereoptimismus für die Laufbahn wird erörtert, und praktische Hinweise zur Förderung von Karriereoptimismus im Karrierecoaching werden gegebe
Keywords: Karrierecoaching; Optimismus; Karriereoptimismus

Laufbahnberatung - Ebner, Katharina; Spurk, Daniel (Lexikon der Berufsbildung, 2016)

Laufbahngestaltung durch Karrierecoaching: Abgrenzung, Methodeneinsatz und Forschungsstand - Ebner, Katharina (Handbuch Karriere und Laufbahnmanagement, 2018)

Longitudinal Effects of Career Adaptability on Job and Career Insecurity via two Types of Perceived Marketability - Spurk, Daniel; Meinecke, Annika; Kauffeld, Simone; Ebner, Katharina (17th Congress of the European Association of Work and Organizational Psychology, 2015)

Ohne Klient kein Coaching. Der Einfluss von Klienteneigenschaften auf die Wirkung von Coaching - Ebner, Katharina (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2014)
Keywords: Coaching

Organisationsentwicklung - Ebner, Katharina; Lang-von Wins, Thomas (Handbuch Medien- und Bildungsmanagement, 2009)

Organisationsentwicklung - Kauffeld, Simone; Ebner, Katharina (Lehrbuch Organisationspsychologie, 2014)

Perceived quality of internships and employability perceptions: The mediating role of career-entry worries - Ebner, Katharina; Soucek, Roman; Selenko, Eva (Education and Training, 2021)
This study illuminates the assumption that internships facilitate labor market entry and answers the question of why internships have a positive effect on students’ self-perceived employability. It is assumed that internships enable more positive employability perceptions by reducing career-entry worries – the worries of not finding a suitable job or not being able to obtain a satisfactory career. A two-wave study among graduate students currently in an internship investigated these relationships. Data on career-entry worries, perceived employability and an evaluation of the internship were collected from 80 students (mean age: 24.6 years, 68% female) from various fields of study aiming at both Bachelor’s and Master’s degrees. The results showed that positively-evaluated internships contributed to graduates’ self-perceived employability by means of reduced career-entry worries over an eight week period. By considering graduates’ career-entry worries – the perceived uncertainty about finding an ‘appropriate’ career in the future – the authors introduce a new concept to the career literature and show that these worries are significant in terms of self-assessed employability.<br

Promoting career optimism and career security during career coaching: development and test of a model - Ebner, Katharina (Coaching, 2019)
This study explores how career coaching contributes to clients’ career optimism and career security from a career resource perspective. Drawing from the Career Resources Model (Hirschi [2012]. The career resources model: An integrative framework for career counsellors. British Journal of Guidance & Counselling, 40(4), 369–383), we propose that career identity resources (self-clarity and career-goal clarity) are essential prerequisites to develop career optimism and career security which are needed to successfully plan and manage careers. Data drawn from a single career coaching intervention for university students served as basis to develop and test a framework linking career identity resources with the psychological career variables career optimism and career security and revealed that working on clients’ self-clarity positively contributes to the development of career-goal clarity, career optimism and career security. The findings additionally outline that the positive effects of career coaching on clients’ career optimism and career security are explained by an increase in career-goal clarity. These results suggest a process model for career coaching interventions.
CRIS-Team Scopus Importer:2020-02-21
Keywords: Career coaching; career insecurity; career optimism; career-goal clarity; coaching model; self-clarity

Promoting positive coaching: Choosing the right focus for feedback to your clients - Ebner, Katharina (FAU Summer School „The Interplay of Work, Health and Organisational Success“, 2014)

Promoting psychological resources for coping with problematic media use: Development and evaluation of a training intervention - Sende, Cynthia; Soucek, Roman; Ebner, Katharina (Computers in Human Behavior Reports, 2025)

Relations of within-person incongruities with life satisfaction and self-efficacy: The moderating role of career coaching - Ebner, Katharina; Spurk, Daniel; Schulte, Eva-Maria; Kauffeld, Simone (International Conference for Well-Being and Performance, 2014)

Standardisiertes Coaching für Nachwuchswissenschaftler und Studierende: Konzeptions- und Implementierungshinweise im Peer-Coaching - Ebner, Katharina (Coaching-Praxisfelder. Forschung und Praxis im Dialog, 2013)

Standardisiertes Coaching für Nachwuchswissenschaftler und Studierende: Konzeptions- und Implementierungshinweise im Peer-Coaching - Ebner, Katharina (Zur Differenzierung von Handlungsfeldern im Coaching. Die Etablierung neuer Praxisfelder, 2016)

Stress durch Email, Whatsapp, Facebook und Co.? – Evaluation eines Trainings zur Reduzierung von digitalem Stress - Sende, Cynthia; Ebner, Katharina (10. Fachgruppentagung Arbeits-, Organisations- und Wirtschaftspsychologie der Deutschen Gesellschaft für Psychologie, 2017)

Stress-reduction without intent: How self-leadership coaching helps to cope with stress - Ebner, Katharina; Schulte, Eva-Maria; Kauffeld, Simone (16th Congress of the European Association of Work and Organizational Psychology, 2013)

The Career Decision-Making Adaptability Score: Exploration and validation of its predictive power for subjective and objective career success - Ebner, Katharina; Paul, Karsten (International Journal for Educational and Vocational Guidance, 2022)
The study aims at validating the Career Decision-Making Adaptability Score (CDA Score) by investigating its predictive influence on objective and subjective career success, career adaptability, and psychological well-being over a 1-year period. Furthermore, the predictive influence of additional career decision-making strategies was scrutinized. Regression analyses of data from 78 employed individuals from two measurement time points demonstrated that the CDA Score predicts yet unexplored variables (e.g., psychological well-being) and consulting with others contributes to career adaptability and satisfaction. The findings extend research on career decision-making, validate the CDA Score longitudinally, and offer directions for the design of career counseling services.
CRIS-Team WoS Importer:2022-05-13

The impact of coaching on maladaptive coping - Ebner, Katharina; Soucek, Roman; Thiele, Lisa (50. Kongress der Deutschen Gesellschaft für Psychologie, 2016)

Toward a better understanding of self‐regulation promoting interventions: when performance management and job crafting meet - Demerouti, Evangelia; Roth, Colin; Ebner, Katharina; Soucek, Roman; Moser, Klaus (Human Resource Management, 2024)
Organizations utilize self-regulation promoting interventions to empower employees in managing challenges and resources autonomously. However, there is limited understanding of how these interventions impact employee task performance and innovative behavior, as well as which processes are critical for their effectiveness. Therefore, a field experiment was conducted to examine the effects of two self-regulation promoting interventions—the Productivity Measurement and Enhancement Systems intervention (ProMES), a job crafting intervention, and their combination—on individual employee performance and innovation through selected process variables. We collected data before, during, and after the interventions over 16 weeks among 123 employees across three experimental and one control group. Consistent with predictions, participants of the ProMES intervention reported a higher level of perceived team climate, which consequently contributed to greater individual innovative behavior. Participants in the job crafting intervention exhibited an increase in job crafting behaviors, which consequently increased innovative behavior and task performance. Unexpectedly, the combined intervention yielded negative effects on both innovative behavior and task performance. The findings suggest that while self-regulation promoting interventions increase favorable outcomes through different mechanisms their combination may impair relevant processes and, more generally, overwhelm employees.

Usability-Test of Competency Certificates. An Empirical Study on Criteria of Further Education Certificates in Human Resource Departments - Ebner, Katharina (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2006)

Validation of the German Career Decision-Making Profile–An Updated 12-Factor Version - Ebner, Katharina; Thiele, Lisa; Spurk, Daniel; Kauffeld, Simone (Journal of Career Assessment, 2016)

Veränderungen durch Coaching: Wie lernt ein Coachee im Coaching-Prozess? - Ebner, Katharina (Qualität im Coaching. Denkanstöße und neue Ansätze: Wie Coaching mehr Wirkung und Klientenzufriedenheit bringt, 2016)

What makes us more employable and successful? Career sponsorship within early academic science careers through networking and career coaching interventions - Spurk, Daniel; Kauffeld, Simone; Ebner, Katharina; Volmer, Judith (International Conference for Well-Being and Performance, 2014)

Why are you enrolled in a non degree-program?“- Exploring personal variables of students in extra-curricular STEM-programs - Muskatewitz, Sara Luisa; Ebner, Katharina (2nd Gender and STEM Conference, 2014)

Why Do Adaptable People Feel Less Insecure? Indirect Effects of Career Adaptability on Job and Career Insecurity via Two Types of Perceived Marketability - Spurk, Daniel; Kauffeld, Simone; Meinecke, M.; Ebner, Katharina (Journal of Career Assessment, 2015)

Worried About Not Finding A Job? A Work Experience Might Help.” Two Country Longitudinal Evidence For The Psychological Effect Of Work Experiences - Ebner, Katharina; Selenko, Eva (18th Congress of the European Association of Work and Organizational Psychology, 2017)